2009
DOI: 10.1590/s0034-72802009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Imunoterapia tópica no tratamento do carcinoma basocelular periocular

Abstract: RESUMOOs autores descrevem um paciente com carcinoma basocelular nodular em canto medial tratado com imiquimode creme 5%. A avaliação patológica de uma biópsia incisional realizada 12 semanas após o tratamento revelou a total resolução da lesão. Embora a cirurgia permaneça como tratamento de primeira escolha, a imunoterapia com imiquimode creme 5% surge como uma opção terapêutica válida para o tratamento ambulatorial do carcinoma basocelular periocular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Immunotherapy lasted from 8 to 16 weeks 8 . Patients reported that each cold-stored sachet with 5% imiquimod cream lasted 3 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy lasted from 8 to 16 weeks 8 . Patients reported that each cold-stored sachet with 5% imiquimod cream lasted 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…Exceptions include a study on patients with BCC in the lower limbs 8 and a study comparing dermatological and non-dermatological services. (9) However, no previous study compared the cost of clinical and surgical treatment of BCC in the periocular area.…”
mentioning
confidence: 99%
“…These markers are molecular target of several marketed drugs. Macedo et al (2009) described a case report about topical immunotherapy for the treatment of periocular basal cell carcinoma and showed that one year after treatment the patient showed no signs of disease recurrence. The Brazilian Journal of Oncology encloses two review articles about several reported tumor markers (Almeida et al, 2007) and tumor markers in breast cancer (Eisenberg and Koifman, 2001) attempting for the importance of clinical diagnostics.…”
Section: Non-specific Therapiesmentioning
confidence: 99%